Menghadapi Tantangan Pendidikan di Era Digital: Strategi dan Solusi (International Forum of Researchers and Lecturers, 2024)
This examines the challenges faced by the world of education in the digital era as well as strategies and solutions to overcome them. The digital era offers great opportunities to improve access and quality of education, but gaps in access to technology, lack of digital literacy, changes in student orientation, teacher reluctance, reduced social interactions, etc., also face many challenges.This article explores strategies to overcome these challenges, including improving technology infrastructure, digital literacy training, developing innovative curricula, implementing hybrid learning, and managing technology use.By working together, governments, schools, teachers, parents, and the private sector can optimizing education in the digital era and creating a more effective and inclusive learning environment.